Cylindrically symmetric eigenfunctions of polarized radiative transfer equation. (March 2019) - Freimanis, J.
Highlights: Expressions for cylindrically symmetric eigenfunctions of polarized RTE proved. Method of semi-analytic modelling of radiation field inside cylinder outlined. Quadratic recurrent relations for Wigner d-functions proved. Abstract: The general expressions for cylindrically symmetric eigenfunctions of polarized radiative transfer equation in homogeneous space obeying Euclidean geometry are derived and proved. The medium is assumed to be statistically homogeneously filled with polydisperse particles, the effective medium (host medium together with particles) is assumed to be isotropic, and birefringence (both linear and circular) is assumed to be negligible.